Comparação dos efeitos de diferentes medicações intracanal no reparo de lesões periapicais em ratos - Klassmann, Larissa Magnus (2013)
In endodontics, the chemomechanical preparation produces a significant reduction in the amount of bacteria in the root canal system. It has been demonstrated that the adjuvant use of intracanal medications, might increase the possibility of success of endodontic therapy. The present study aimed to evaluate the effectiveness of different intracanal medications, when used alone or in combination, in a rat model of periapical lesions. This thesis was divided into three chapters, according to the scientific articles. The Chapter 1 emphasizes the methodology used, which employed Cone Beam Tomography to measure the repair of periapical lesions after endodontic therapy and root canal dressing, demonstrating the effectiveness of this tool. Calcium hydroxide was tested, versus control group, which had received no medication. The lesion area was 9.38 ± 0.68 mm2 in the control group, and 7.08 ± 0.44 mm2 in the treated group (p<0.05), according to CBTC evaluation. This data was confirmed by histological evaluation, indicating the applicability of CBTC in the rat model of apical periodontitis. The Chapter 2 evaluated the natural compound resveratrol, and the medications considered as gold standards in Endodontics, chlorhexidine and calcium hydroxide, in isolated schemes or in associations. The effects of resveratrol were also assessed in combination to vitamin E or rice oil, which also have known antioxidant effects. In this paper, the comparison between treated and control groups showed significant differences in the groups that received calcium hydroxide, resveratrol in propyleneglycol or resveratrol with chlorhexidine with inhibition percentages of about 25%. The effects of medications were confirmed by qualitative histological analysis, which showed higher inflammatory infiltrate, areas of resorption and suppuration in the control groups. The Chapter 3 shows data on the use of amoxicillin as intracanal medication, when used alone or in combined protocols. In this study, amoxicillin was highly effective, presenting significant differences when tested alone or in combination with calcium hydroxide or chlorhexidine. Amoxicillin vehicled in propyleneglycol produced an inhibition of 47 ± 5% of periapical lesion areas, and a similar degree of reduction was observed in the group that received amoxicillin plus chlorhexidine gluconate (46 ± 5%). Notably, the combination of amoxicillin and calcium hydroxide paste resulted in a marked inhibition of periapical lesions (65 ± 10 %). Qualitative H&E histological analysis showed that inflammatory infiltrate ranged from mild to moderate in the test groups, and the control samples presented intense inflammatory infiltrate, with visible resorption areas. Regarding the Mallory staining, it was possible to observe a massive presence of fibroblasts, surrounded by intact and well-bonded collagen fibers. Otherwise, the control groups showed intense inflammatory infiltrate and areas of abscess. There is a final chapter with a general discussion and some specific considerations on the various strategies tested herein and the meaning of our study for Endodontics. In conclusion, the CBTC might represent an important tool for studies in pre-clinical endodontics, showing applicability for measuring changes in the apical region. Furthermore, either the antioxidant resveratrol, or the antibiotic amoxicillin, appear to be useful strategies as alternative intracanal dressings.